Across Borders of Patriarchy: A Comparative Feminist Study of Emily Brontë’s Wuthering Heights and Parijat’s Blue Mimosa - Ghimire, Sushil (Mindscape: A Journal of English & Cultural Studies, 2025)
This study examines Emily Brontë’s Wuthering Heights (1848) and Parijat’s Blue Mimosa (1965), two debut novels written more than a century apart, in different worlds, yet connected by a shared portrayal of women’s suffering under patriarchal authority. The research explores how Catherine Earnshaw and Sakambari embody experiences of oppression, discrimination, and premature tragedy as consequences of deeply rooted gender hierarchies. The study adopts a qualitative approach, guided specifically by de Beauvoir’s concept of woman as the “Other” in The Second Sex (1949). According to de Beauvoir, patriarchal societies construct women as secondary, subordinate beings defined in relation to men. Applying this framework, the analysis explores how Brontë and Parijat represent their heroines as trapped in gendered hierarchies yet simultaneously striving for selfhood and autonomy. The findings reveal that although Brontë was writing in nineteenth-century England and Parijat in twentieth-century Nepal, both texts depict strikingly similar patterns of female marginalization, particularly within family structures. Catherine and Sakambari resist patriarchal expectations in distinct ways-Catherine by questioning marital conformity and Sakambari by refusing to conform to prescriptive feminine norms-thereby asserting women’s agency while highlighting the universality of patriarchal oppression. By situating Wuthering Heights and Blue Mimosa in a cross-cultural and transnational dialogue, this study contributes to comparative feminist literary scholarship. It demonstrates how women writers, despite temporal and spatial distance, articulate parallel experiences of oppression and resistance, affirming the role of literature as a powerful medium for feminist critique and consciousness.